A step forward in the sigma enigma: a role for chirality in the sigma1 receptor–ligand interaction?. Issue 1 (17th October 2014) - Rossi, Daniela; Marra, Annamaria; Rui, Marta; Laurini, Erik; Fermeglia, Maurizio; Pricl, Sabrina; Schepmann, Dirk; Wuensch, Bernhard; Peviani, Marco; Curti, Daniela; Collina, Simona
Abstract : To investigate the role of chirality in the ligand–σ1 receptor interaction, a series of enantiomeric arylalkylaminoalcohols and arylpyrrolidinols was evaluated by means of both in silico and in vitro studies. Abstract : In our recent research racemicRC-33 was identified as a potent and highly promising σ1 receptor agonist, showing excellent σ1 receptor affinity and promoting NGF-induced neurite outgrowth in PC12 cells at very low concentrations. Surprisingly, both its interaction with the biological target and its effect on neurite sprouting proved to be non-stereoselective. Starting from the observation that a hydrogen bond center in the scaffold of a σ1 ligand is an important pharmacophoric element for receptor/ligand interaction, we hypothesized that the absence of such pharmacophoric feature in the structure ofRC-33 could be also responsible for the lack of enantioselectivity in its interaction with the target receptor. To verify our hypothesis, in this paper we evaluated – both in silico and in vitro – the ability of a series of enantiomeric arylalkylaminoalcohols and arylpyrrolidinols1–5 to interact with the receptor. All these compounds are structurally related toRC-33 and are characterized by the presence of an –OH group as the additional pharmacophore feature. Interestingly, the results of our study show that the σ1 receptor exhibits enantiopreference toward compounds characterized by ( S )-configuration at the stereogenic center bearing the aromatic moiety only when the alcoholic group is also present at that chiral center, thus supporting our original hypothesis.